Synthesis, Characterization, and Antibacterial Activity Study of Novel Curcuminoids Derivatives - M. AL-Hakiem, Mustafa; Q. Alderawy, Mustafa; Adnan, Riham; S Elias, Rita (Iraqi Journal of Pharmaceutical Sciences, 2024)
Curcumin is a well-known compound with broad spectrum biological activities, but unfortunately rapid degradation properties and low bioavailability. Therefore, several attempts have been made to overcome these obstructions through chemical modifications. This investigation aimed to prepare several curcuminoids and their pyrazole derivatives and study their antibacterial activity. Curcuminoids and their pyrazole derivatives were synthesized, and their Chemical structures were established from their mass, 1H NMR, and 13C NMR spectra, followed by an in vitro study of the antibacterial activity of these compounds against the gram-negative Escherichia coli and the gram-positive Staphylococcus aureus using disc diffusion method. No compound has recorded any activity against Escherichia coli, while compounds 1-9 have shown anti-staphylococcus activity, compounds 11-14 didn’t present any activity, and compound 10 shows activity at the lowest studied concentration only. These findings suggest that the pyrazole substitution on curcumin derivatives that do not bear an aromatic hydroxyl group would diminish their anti-staphylococcal activity. More antibacterial activity studies are suggested regarding compound 10 activity